2023
DOI: 10.3389/fmicb.2023.1295215
|View full text |Cite
|
Sign up to set email alerts
|

Winds of change a tale of: asthma and microbiome

David Galeana-Cadena,
Itzel Alejandra Gómez-García,
Karen Gabriel Lopez-Salinas
et al.

Abstract: The role of the microbiome in asthma is highlighted, considering its influence on immune responses and its connection to alterations in asthmatic patients. In this context, we review the variables influencing asthma phenotypes from a microbiome perspective and provide insights into the microbiome’s role in asthma pathogenesis. Previous cohort studies in patients with asthma have shown that the presence of genera such as Bifidobacterium, Lactobacillus, Faecalibacterium, and Bacteroides in the gut microbiome has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 246 publications
0
2
0
Order By: Relevance
“…This leads to a higher production of immunoglobulin E (IgE) and eosinophilic inflammation [ 5 , 6 , 7 ]. Research has demonstrated that children with food allergies and/or atopic dermatitis are more likely to develop asthma later in life [ 8 , 9 , 10 ]. This is known as the ‘atopic march’ [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a higher production of immunoglobulin E (IgE) and eosinophilic inflammation [ 5 , 6 , 7 ]. Research has demonstrated that children with food allergies and/or atopic dermatitis are more likely to develop asthma later in life [ 8 , 9 , 10 ]. This is known as the ‘atopic march’ [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that children with food allergies and/or atopic dermatitis are more likely to develop asthma later in life [8][9][10]. This is known as the 'atopic march' [11].…”
Section: Introductionmentioning
confidence: 99%